2016
DOI: 10.1245/s10434-016-5210-7
|View full text |Cite
|
Sign up to set email alerts
|

Additional Cavity Shaving at the Time of Breast-Conserving Surgery Enhances Accuracy of Margin Status Examination

Abstract: Shaving does not significantly decrease the re-excision rate but provides wider clear margins in most procedures. It ensures more accurate margin examination and decreases false-positive margin rate, without any increase in removed breast-tissue volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Our findings regarding the frozen section's sensitivity and specificity in BCS were in agreement with systematic reviews of Esbona et al and John et al (14,58). Also, many cohort studies and national databases have examined the diagnostic value of this method (59)(60)(61).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings regarding the frozen section's sensitivity and specificity in BCS were in agreement with systematic reviews of Esbona et al and John et al (14,58). Also, many cohort studies and national databases have examined the diagnostic value of this method (59)(60)(61).…”
Section: Discussionsupporting
confidence: 92%
“…Four studies reported data on locoregional recurrence [15,27,32,37]. The pooled incidence of locoregional recurrence for the CS group was 3.0% (95% CI 2.0–4.5%), and for the standard partial mastectomy group was 4.0% (95% CI 1.1–13.4%).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were eligible for data synthesis [15,27,32,33]. The pooled data revealed that CS did not have a significantly increased volume of excised tissue compared with BCS alone, with a high level of heterogeneity (WMD = −23.88, 95% CI −55.20 to 7.44, P = 0.14; I 2 = 77.7%, P < 0.05) (Fig 6).…”
Section: Resultsmentioning
confidence: 99%
“…We have not a clear explanation for the discrepancy between international (and ours) RBS rates and those released by the PNE. We are aware of only two published papers in Italy of BCS with cavity shaving vs. not reporting RBS rates of 1.9% vs. 10.6%, and 14.3% vs. 18.9%, respectively [ 39 , 40 ]. It is too early to evaluate oncological safety, but the local relapse rate at 2 years in the current series is reassuring (0.6%) and consistent with that of our previous series operated between 2000 and 2009 (2.9% at 4 years) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%